Seamlessly Integrating Advanced Analytics and AI Technologies to Transform Financial Systems and Drive Strategic Excellence - Lakshminarayana Reddy Kothapalli Sondinti; Kanthety Sundeep Saradhi (Utilitas Mathematica, 2024)
The rise of advanced analytics and artificial intelligence (AI) technologies has created a new world of opportunities that are transforming financial systems. The next wave of financial solutions comes from seamlessly integrating financial applications with advanced analytics and AI. The main goal is to refine or redesign existing tasks to better reflect the specific tasks and decisions performed most frequently. It is clear that finance systems need to better integrate such technological solutions. It is necessary to refine or redesign tasks, making traditional and AI solutions more closely linked. AI-driven financial applications can deliver operational efficiency for financial systems, as well as enable identification of potential strategic business opportunities. These take full advantage of AI-enabled methods using neural networks that promote self-learning and improve with new input. Integrating AI technologies into financial systems purposes to refine or redesign these systems to link tasks to the potential decisions they are required for. This ensures financial solutions are introduced that can facilitate decisions more effectively and optimise optimal outcomes. Seamless integration is achieved via a generic method for translating well-designed tasks into a feature space that best reflects the decisions. Possible decisions are fast and automatically facilitated. Critical challenges and opportunities for seamless integration are discussed. These financial systems and corresponding technologies are evaluated through in-depth customer focus groups and case studies of two European banks. For developing new financial solutions, banks collaborate best with fintech providers and AI research institutions, with technology and competitive advantage being the most important criteria. Both banks recognise the importance of AI technology for the future transformation of financial systems and provide infrastructure support for the integration of it.